```------------------------------------------------------------------------
-- A simple tactic for proving equality of equality proofs
------------------------------------------------------------------------

{-# OPTIONS --without-K #-}

open import Equality

module Equality.Tactic
{reflexive} (eq : ∀ {a p} → Equality-with-J a p reflexive) where

open Derived-definitions-and-properties eq
open import Prelude hiding (Level; lift; lower)

------------------------------------------------------------------------
-- Equality expressions

-- Equality expressions.
--
-- Note that the presence of the Refl constructor means that Eq is a
-- definition of equality with a concrete, evaluating eliminator.

data Eq {a} {A : Set a} : A → A → Set (lsuc a) where
Lift  : ∀ {x y} (x≡y : x ≡ y) → Eq x y
Refl  : ∀ {x} → Eq x x
Sym   : ∀ {x y} (x≈y : Eq x y) → Eq y x
Trans : ∀ {x y z} (x≈y : Eq x y) (y≈z : Eq y z) → Eq x z
Cong  : ∀ {B : Set a} {x y}
(f : B → A) (x≈y : Eq x y) → Eq (f x) (f y)

-- Semantics.

⟦_⟧ : ∀ {a} {A : Set a} {x y : A} → Eq x y → x ≡ y
⟦ Lift x≡y      ⟧ = x≡y
⟦ Refl          ⟧ = refl _
⟦ Sym x≈y       ⟧ = sym ⟦ x≈y ⟧
⟦ Trans x≈y y≈z ⟧ = trans ⟦ x≈y ⟧ ⟦ y≈z ⟧
⟦ Cong f x≈y    ⟧ = cong f ⟦ x≈y ⟧

-- A derived combinator.

Cong₂ : ∀ {a} {A B C : Set a} (f : A → B → C) {x y : A} {u v : B} →
Eq x y → Eq u v → Eq (f x u) (f y v)
Cong₂ f {y = y} {u} x≈y u≈v =
Trans (Cong (flip f u) x≈y) (Cong (f y) u≈v)

private

Cong₂-correct :
∀ {a} {A B C : Set a} (f : A → B → C) {x y : A} {u v : B}
(x≈y : Eq x y) (u≈v : Eq u v) →
⟦ Cong₂ f x≈y u≈v ⟧ ≡ cong₂ f ⟦ x≈y ⟧ ⟦ u≈v ⟧
Cong₂-correct f x≈y u≈v = refl _

------------------------------------------------------------------------
-- Simplified expressions

private

-- The simplified expressions are stratified into three levels.

data Level : Set where
upper middle lower : Level

-- Bottom layer: a single use of congruence applied to an actual
-- equality.

data EqS-lower {a} {A : Set a} : A → A → Set (lsuc a) where
Cong : {B : Set a} {x y : B} (f : B → A) (x≡y : x ≡ y) →
EqS-lower (f x) (f y)

-- Middle layer: at most one use of symmetry.

data EqS-middle {a} {A : Set a} : A → A → Set (lsuc a) where
No-Sym : ∀ {x y} (x≈y : EqS-lower x y) → EqS-middle x y
Sym    : ∀ {x y} (x≈y : EqS-lower x y) → EqS-middle y x

-- Uppermost layer: a sequence of equalities, combined using
-- transitivity and a single use of reflexivity.

data EqS-upper {a} {A : Set a} : A → A → Set (lsuc a) where
Refl : ∀ {x} → EqS-upper x x
Cons : ∀ {x y z} (x≈y : EqS-middle x y) (y≈z : EqS-upper y z) →
EqS-upper x z

-- Simplified expressions.

EqS : ∀ {a} {A : Set a} → Level → A → A → Set (lsuc a)
EqS lower  = EqS-lower
EqS middle = EqS-middle
EqS upper  = EqS-upper

-- Semantics of simplified expressions.

⟦_⟧S : ∀ {ℓ a} {A : Set a} {x y : A} → EqS ℓ x y → x ≡ y
⟦_⟧S {lower}  (Cong f x≡y)   = cong f x≡y
⟦_⟧S {middle} (No-Sym x≈y)   =     ⟦ x≈y ⟧S
⟦_⟧S {middle} (Sym    x≈y)   = sym ⟦ x≈y ⟧S
⟦_⟧S {upper}  Refl           = refl _
⟦_⟧S {upper}  (Cons x≈y y≈z) = trans ⟦ x≈y ⟧S ⟦ y≈z ⟧S

-- Simplified expressions which are equivalent to a given proof.

EqS_⟨_⟩ : Level → ∀ {a} {A : Set a} {x y : A} → x ≡ y → Set (lsuc a)
EqS ℓ ⟨ x≡y ⟩ = ∃ λ (x≈y : EqS ℓ _ _) → x≡y ≡ ⟦ x≈y ⟧S

------------------------------------------------------------------------
-- Manipulation of expressions combined with proofs

private

lift : ∀ {a} {A : Set a} {x y : A}
(x≡y : x ≡ y) → EqS upper ⟨ x≡y ⟩
lift x≡y = Cons (No-Sym (Cong id x≡y)) Refl , (
x≡y                           ≡⟨ cong-id _ ⟩
cong id x≡y                   ≡⟨ sym (trans-reflʳ _) ⟩∎
trans (cong id x≡y) (refl _)  ∎)

snoc : ∀ {a} {A : Set a} {x y z : A} {x≡y : x ≡ y} {y≡z : y ≡ z} →
EqS upper  ⟨ sym            y≡z  ⟩ →
EqS middle ⟨ sym        x≡y      ⟩ →
EqS upper  ⟨ sym (trans x≡y y≡z) ⟩
snoc {x≡y = x≡y} {y≡z} (Refl , h₁) (y≈z , h₂) = Cons y≈z Refl , (
sym (trans x≡y y≡z)        ≡⟨ sym-trans _ _ ⟩
trans (sym y≡z) (sym x≡y)  ≡⟨ cong₂ trans h₁ h₂ ⟩
trans (refl _) ⟦ y≈z ⟧S    ≡⟨ trans-reflˡ _ ⟩
⟦ y≈z ⟧S                   ≡⟨ sym (trans-reflʳ _) ⟩∎
trans ⟦ y≈z ⟧S (refl _)    ∎)
snoc {x≡y = x≡y} {y≡z} (Cons x≈y y≈z , h₁) (z≈u , h₂)
with snoc (y≈z , sym-sym _) (z≈u , h₂)
... | (y≈u , h₃) = Cons x≈y y≈u , (
sym (trans x≡y y≡z)                                    ≡⟨ sym-trans _ _ ⟩
trans (sym y≡z) (sym x≡y)                              ≡⟨ cong₂ trans h₁ (refl (sym x≡y)) ⟩
trans (trans ⟦ x≈y ⟧S ⟦ y≈z ⟧S) (sym x≡y)              ≡⟨ trans-assoc _ _ _ ⟩
trans ⟦ x≈y ⟧S (trans ⟦ y≈z ⟧S (sym x≡y))              ≡⟨ cong (trans ⟦ x≈y ⟧S) \$
cong₂ trans (sym (sym-sym ⟦ y≈z ⟧S)) (refl (sym x≡y)) ⟩
trans ⟦ x≈y ⟧S (trans (sym (sym ⟦ y≈z ⟧S)) (sym x≡y))  ≡⟨ cong (trans _) \$ sym (sym-trans x≡y (sym ⟦ y≈z ⟧S)) ⟩
trans ⟦ x≈y ⟧S (sym (trans x≡y (sym ⟦ y≈z ⟧S)))        ≡⟨ cong (trans _) h₃ ⟩∎
trans ⟦ x≈y ⟧S ⟦ y≈u ⟧S                                ∎)

append : ∀ {a} {A : Set a} {x y z : A} {x≡y : x ≡ y} {y≡z : y ≡ z} →
EqS upper ⟨       x≡y     ⟩ →
EqS upper ⟨           y≡z ⟩ →
EqS upper ⟨ trans x≡y y≡z ⟩
append {x≡y = x≡y} {y≡z} (Refl , h) x≈y =
Σ-map id
(λ {y≈z} y≡z≡⟦y≈z⟧ →
trans x≡y y≡z            ≡⟨ cong₂ trans h y≡z≡⟦y≈z⟧ ⟩
trans (refl _) ⟦ y≈z ⟧S  ≡⟨ trans-reflˡ _ ⟩∎
⟦ y≈z ⟧S                 ∎)
x≈y
append {x≡y = x≡z} {z≡u} (Cons x≈y y≈z , h) z≈u =
Σ-map (Cons x≈y)
(λ {y≈u} trans⟦y≈z⟧z≡u≡⟦y≈u⟧ →
trans x≡z z≡u                        ≡⟨ cong₂ trans h (refl z≡u) ⟩
trans (trans ⟦ x≈y ⟧S ⟦ y≈z ⟧S) z≡u  ≡⟨ trans-assoc _ _ _ ⟩
trans ⟦ x≈y ⟧S (trans ⟦ y≈z ⟧S z≡u)  ≡⟨ cong (trans _) trans⟦y≈z⟧z≡u≡⟦y≈u⟧ ⟩∎
trans ⟦ x≈y ⟧S ⟦ y≈u ⟧S              ∎)
(append (y≈z , refl _) z≈u)

map-sym : ∀ {a} {A : Set a} {x y : A} {x≡y : x ≡ y} →
EqS middle ⟨ x≡y ⟩ → EqS middle ⟨ sym x≡y ⟩
map-sym {x≡y = x≡y} (No-Sym x≈y , h) = Sym    x≈y , (sym x≡y       ≡⟨ cong sym h ⟩∎
sym ⟦ x≈y ⟧S  ∎)
map-sym {x≡y = x≡y} (Sym    x≈y , h) = No-Sym x≈y , (sym x≡y             ≡⟨ cong sym h ⟩
sym (sym ⟦ x≈y ⟧S)  ≡⟨ sym-sym _ ⟩∎
⟦ x≈y ⟧S            ∎)

reverse : ∀ {a} {A : Set a} {x y : A} {x≡y : x ≡ y} →
EqS upper ⟨     x≡y ⟩ →
EqS upper ⟨ sym x≡y ⟩
reverse {x≡y = x≡y} (Refl         , h) = Refl , (sym x≡y       ≡⟨ cong sym h ⟩
sym (refl _)  ≡⟨ sym-refl ⟩∎
refl _        ∎)
reverse {x≡y = x≡y} (Cons x≈y y≈z , h)
with snoc (reverse (y≈z , refl _)) (map-sym (x≈y , refl _))
... | (x≈z , h′) = x≈z , (sym x≡y                        ≡⟨ cong sym h ⟩
sym (trans ⟦ x≈y ⟧S ⟦ y≈z ⟧S)  ≡⟨ h′ ⟩∎
⟦ x≈z ⟧S                       ∎)

map-cong : ∀ {ℓ a} {A B : Set a} {x y : A}
(f : A → B) {x≡y : x ≡ y} →
EqS ℓ ⟨ x≡y ⟩ → EqS ℓ ⟨ cong f x≡y ⟩
map-cong {lower}  f {gx≡gy} (Cong g x≡y   , h) = Cong (f ∘ g) x≡y , (cong f gx≡gy         ≡⟨ cong (cong f) h ⟩
cong f (cong g x≡y)  ≡⟨ cong-∘ f g _ ⟩∎
cong (f ∘ g) x≡y     ∎)
map-cong {middle} f {x≡y}   (No-Sym x≈y   , h) = Σ-map No-Sym id (map-cong f (x≈y , h))
map-cong {middle} f {x≡y}   (Sym    x≈y   , h) = Σ-map Sym (λ {fy≈fx} cong-f-⟦x≈y⟧≡⟦fy≈fx⟧ →
cong f x≡y             ≡⟨ cong (cong f) h ⟩
cong f (sym ⟦ x≈y ⟧S)  ≡⟨ cong-sym f _ ⟩
sym (cong f ⟦ x≈y ⟧S)  ≡⟨ cong sym cong-f-⟦x≈y⟧≡⟦fy≈fx⟧ ⟩∎
sym ⟦ fy≈fx ⟧S         ∎)
(map-cong f (x≈y , refl _))
map-cong {upper}  f {x≡y}   (Refl         , h) = Refl , (cong f x≡y       ≡⟨ cong (cong f) h ⟩
cong f (refl _)  ≡⟨ cong-refl f ⟩∎
refl _           ∎)
map-cong {upper}  f {x≡y}   (Cons x≈y y≈z , h)
with map-cong f (x≈y , refl _) | map-cong f (y≈z , refl _)
... | (fx≈fy , h₁) | (fy≈fz , h₂) = Cons fx≈fy fy≈fz , (
cong f x≡y                                 ≡⟨ cong (cong f) h ⟩
cong f (trans ⟦ x≈y ⟧S ⟦ y≈z ⟧S)           ≡⟨ cong-trans f _ _ ⟩
trans (cong f ⟦ x≈y ⟧S) (cong f ⟦ y≈z ⟧S)  ≡⟨ cong₂ trans h₁ h₂ ⟩∎
trans ⟦ fx≈fy ⟧S ⟦ fy≈fz ⟧S                ∎)

-- Equality-preserving simplifier.

simplify : ∀ {a} {A : Set a} {x y : A}
(x≡y : Eq x y) → EqS upper ⟨ ⟦ x≡y ⟧ ⟩
simplify (Lift x≡y)      = lift x≡y
simplify Refl            = (Refl , refl _)
simplify (Sym x≡y)       = reverse (simplify x≡y)
simplify (Trans x≡y y≡z) = append (simplify x≡y) (simplify y≡z)
simplify (Cong f x≡y)    = map-cong f (simplify x≡y)

------------------------------------------------------------------------
-- Tactic

abstract

-- Simple tactic for proving equality of equality proofs.

prove : ∀ {a} {A : Set a} {x y : A} (x≡y x≡y′ : Eq x y) →
⟦ proj₁ (simplify x≡y) ⟧S ≡ ⟦ proj₁ (simplify x≡y′) ⟧S →
⟦ x≡y ⟧ ≡ ⟦ x≡y′ ⟧
prove x≡y x≡y′ hyp =
⟦ x≡y ⟧                     ≡⟨ proj₂ (simplify x≡y) ⟩
⟦ proj₁ (simplify x≡y ) ⟧S  ≡⟨ hyp ⟩
⟦ proj₁ (simplify x≡y′) ⟧S  ≡⟨ sym (proj₂ (simplify x≡y′)) ⟩∎
⟦ x≡y′ ⟧                    ∎

------------------------------------------------------------------------
-- Some examples

private
module Examples {A : Set} {x y : A} (x≡y : x ≡ y) where

ex₁ : trans (refl x) (sym (sym x≡y)) ≡ x≡y
ex₁ = prove (Trans Refl (Sym (Sym (Lift x≡y)))) (Lift x≡y) (refl _)

ex₂ : cong proj₂ (sym (cong (_,_ x) x≡y)) ≡ sym x≡y
ex₂ = prove (Cong proj₂ (Sym (Cong (_,_ x) (Lift x≡y))))
(Sym (Lift x≡y))
(refl _)

-- Non-examples: The tactic cannot prove trans-symˡ or trans-symʳ.
```